Brand representation and symbolism understanding – perceived differences among young consumers - Brzovska, Ezheni; Debarliev, Stojan; Ozretic, Doshen, Dzurzana (EMAC regional, 2020)
The purpose of the paper is to understand whether children of different ethnicity, age and gender relate to brand logos in different ways in term of brand representation and brand symbolism. Children begin to understand symbolic aspects of consumption at early age, enhancing the importance to observe and explain certain pattern of behavior in very young children. The paper extends existing research by including more diverse sample of children with different ethnic background and the research was administered across three testing sessions, assessing level of brand representation and symbolism in children aged 3 to 5 years. The findings indicated that brand representation and understanding brand symbolism commences at an early age. Differences in the perceptions among children with different demographic characteristic were identified, with potential implication on the effects of branding.
Keywords: Brand symbolism, young children, brand representation